Ketertarikan konsumen wanita terhadap riview produk oleh beauty vlogger - Oktafia, Putri Ayu (Universitas Negeri Surabaya, 2022)
With the widespread presence of beauty products among the public, there are various kinds of advantages and disadvantages of a beauty product issued by a beauty brand company. Therefore, consumer interest in an item is determined by a review from a beauty vlogger. The beauty vlogger here has the role of providing information on a beauty product that is currently viral or trending in the beauty world with a true assessment according to the facts. This type of research is quantitative research using Google form media which is given to the public, with 22 respondents. The results of this study indicate that beauty vloggers have an important role for female consumers who want to buy a beauty product.Keywords: Beauty Vlogger Reviews, Beauty Products, Female Consumers